Media international Australia - Australian Film, Television and Radio School (North Ryde, N.S.W. : Australian Film Television & Radio School, 1995)
Media International Australia publishes new scholarly and applied research on the media, telecommunications, and the cultural industries, and the policy regimes within which they operate. Broadly inclusive and interdisciplinary, the journal publishes the writing of history, theory and analysis, commentary and debate. While its primary focus is Australia, the journal also aims to provide an international perspective. MIA was founded by Professor Henry Mayer in 1976. It was published by the Australian Film, Television and Radio School until 1997, when it moved to the Centre for Cultural and Media Policy at Griffith University. At that time, it was merged with the Centre's journal, Culture and Policy.
Also available in printed form.
Journal.
Keywords: Mass media -- Social aspects -- Periodicals; Communication -- Australia -- Periodicals; Mass media -- Australia -- Periodicals; Australia -- Cultural policy -- Periodicals